The Relationship of Training, Work Commitment, and Work Behaviour on Career Development of Police Officers in Jatiasih - Somantri, Nurcahyani Dewigita; Shiratina, Aldina (Jurnal Manajemen Sinergi, 2024)
Objective: The aim of this study is to investigate the effects of training, job dedication, and work behaviour on career progression. This study's sample included 41 police officers from the Sector Police (Polsek) of Jatihasih Village, Jatiasih District, Bekasi City, West Java Province.Methodology: This research was analyzed statistically using SEM Smart PLS 4.0, namely a multivariate analysis method whose focus is statistical analysis involving measurements and variables.Findings: At a 5% confidence level, hypotheses H1, H2, and H3 are accepted. Work attitude is the most influential variable (as measured by its coefficient value).Conclusion: This study showed that training had a good and significant impact on career development. Work Commitment has a favourable and significant impact on career development. This implies that workplace behaviour has a favourable and significant impact on career advancement. The most important work behaviour to remember while on duty in the field is to nurture, protect, and aid the community.